2013
DOI: 10.1177/1524838013515759
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Types of Screening Tool Administration Methods Used for the Detection of Intimate Partner Violence

Abstract: Intimate partner violence (IPV) is associated with significant health consequences for victims, including acute/chronic pain, depression, trauma, suicide, death, as well as physical, emotional, and mental harms for families and children. The objective of this systematic review and meta-analysis was to assess the rate of IPV disclosure in adult women (>18 years of age) with the use of three different screening tool administration methods: computer-assisted self-administered screen, self-administered written scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 17 publications
0
44
0
2
Order By: Relevance
“…Additionally, it should be emphasized that screening for IPV is itself an intervention, as detection and referral to appropriate community resources have significant impact. Recent research indicates computer screening may increase IPV disclosures as well as IPV discussions between physicians and patients and the amount of services provided [27]. Perceived workplace support for IPV response as well as practice-related resources (e.g., community referrals, an IPV response protocol) appear to facilitate ob-gyn preparedness to respond to IPV.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it should be emphasized that screening for IPV is itself an intervention, as detection and referral to appropriate community resources have significant impact. Recent research indicates computer screening may increase IPV disclosures as well as IPV discussions between physicians and patients and the amount of services provided [27]. Perceived workplace support for IPV response as well as practice-related resources (e.g., community referrals, an IPV response protocol) appear to facilitate ob-gyn preparedness to respond to IPV.…”
Section: Resultsmentioning
confidence: 99%
“…41,42 Computer-based surveys have been shown to be acceptable to adults and to elicit more truthful responses on some sensitive health issues than in-person interviews. [43][44][45][46] Though providers may hesitate to use electronic surveys to elicit information on what could be sensitive topics, research in health care settings has shown greater disclosure by adolescents, adults, and adult caregivers via computer-based screenings versus face-to-face interviews on highly sensitive items surrounding substance use, sexual behavior, and intimate partner violence, [46][47][48][49][50][51][52][53][54][55][56][57] with some of this work done in ED settings. 50,58 In line with results from the current study, other studies have found little difference in reporting rates for less sensitive items across these formats.…”
Section: Discussionmentioning
confidence: 99%
“…Some participants completed the questionnaire themselves and some participants had assistance from a social worker, which could have influenced the results. However, a recent systematic review showed that there are no significant differences in disclosure rate when women were screened in face-to-face interviews or with a self-administered written questionnaire [30]. The prevalence of IPV may be underreported amongst married women since it is possible that married women living in a current abusive relationship are less likely to attend such an event.…”
Section: Discussionmentioning
confidence: 99%